Peri-Urban Pressures: The Interplay of Land Strategies and Urbanization in Algeria’s Oran Metropolis - Hayette Nemouchi (Journal of Contemporary Urban Affairs, 2023)
In contemporary times, the worldwide trend of urban expansion has become an inexorable force. This article engages in a comprehensive examination of the intricate dynamics surrounding urban sprawl and land utilization within the peri-urban regions of significant Algerian municipalities, with a specific focus on the city of Oran. Employing a methodology rooted in social geography, this study deploys a trio of investigative approaches: documentary analysis, spatio-temporal scrutiny of peri-urban domains, and in-situ field investigations to shed light on the intricate intricacies of land ownership dynamics in the context of urban sprawl. The swift development of the Oran metropolis, along with its manifold ramifications, underscores a profound disconnection between the aspirations of political stakeholders and the unfolding urban milieu. This article accentuates the pivotal role of land as a coveted resource profoundly influencing the contours of emerging urban regions. In response to these emerging challenges, Algeria must adopt integrated land and urban planning strategies that foster harmonious and sustainable urban development. This necessitates a comprehensive vision for metropolitan regions, a departure from sectoral planning that subordinates agriculture to industrial and urban considerations, and the formulation of efficient and coordinated urban planning instruments. Within this intricate nexus of urban and rural development, the urban sprawl's encroachment upon rural landscapes mandates a strategic approach to attain equilibrium and coherence within the urban fabric.